Strategies for Accelerating Stunting Reduction in Toddlers - Nurdiyan; Sholihah, Qomariatus; Maharani Pertiwi K; Atikawati, Dini (Sekolah Pascasarjana Universitas Brawijaya, 2025)
Stunting hurts the physical growth of toddlers. Several contributing factors to stunting include nutritional aspects, exclusive breastfeeding practices, educational levels, maternal knowledge, and a history of low birth weight (BBLR). Efforts to support adequate dietary intake for children require mothers' capabilities in providing caregiving and ensuring a healthy family environment's sanitation. To enhance the handling of stunting, the Indonesian government issued Presidential Regulation No. 72 of 2021, titled